Phenotypic and Genotypic Characterization of Escherichia coli and Salmonella spp. Isolates from Pigs at Slaughterhouse and from Commercial Pork Meat in Portugal - Carlota Gonçalves; Leonor Silveira; João Rodrigues; Rosália Furtado; Sónia Ramos; Alexandra Nunes; Ângela Pista (MDPI AG, 2024)
Background: Foodborne diseases are a serious public health concern, and food-producing animals are a major source of contamination. Methods: The present study analysed Escherichia coli and Salmonella spp. isolated from faecal samples of 100 fattening pigs and from 52 samples of pork meat. Results: The results showed that the majority of the analysed meat samples were considered satisfactory in terms of microbiological quality (92.3% for E. coli and 94.2% for Salmonella spp.). Salmonella spp. was identified in 5.8% of the meat samples, whereas E. coli was detected in 89.5% of all samples (69.2% in meat and 100% in faecal samples). Furthermore, 1.9% of the faecal samples contained Shiga-toxin-producing E. coli and 3.9% contained enterotoxigenic E. coli. All sequenced isolates presented virulence genes for extraintestinal pathogenic E. coli. Moreover, 75.0% of E. coli isolates from meat and 71.8% from faeces samples showed antibiotic resistance, with 40.7% and 51.4%, respectively, being multidrug-resistant (MDR). The most prevalent resistances were to tetracycline, ampicillin, and sulfamethoxazole, and one E. coli isolate showed resistance to extended-spectrum β-lactamase. Conclusions: This study highlights the role of pigs as a potential source of human contamination and the importance of a One Health approach to ensure food safety and to promote public health.